A Comparative Analysis of Key Integration Blocks - Jasiński, Leszek Jerzy (Comparative Economic Research. Central and Eastern Europe, 2024)
Why is integration progressing successfully in some parts of the world but not in others? Why are only some integration blocks hugely important for member countries? And why this is not the case globally? This article provides a comparative analysis of international economic structures, aiming to identify the factors that contribute to the validity and effectiveness of integration. The article examines eight economic blocks: the European Union, the Agreement between the United States of America, the United Mexican States and Canada, the Southern Common Market, the Association of Southeast Asian Nations, the Euroasian Economic Union, the South Asian Association for Regional Cooperation, the African Union, and the Regional Comprehensive Economic Partnership. We take into account five stages of integration: free trade area, customs union, single market, economic union, and monetary union. To understand the progress of integration, one must consider a number of developments and indicators. The coefficient of economic gravity, which we describe in this paper, is a convenient method to find out how important integration structures are for contracting states.